(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2018)
Without a common format, the financial community has been constantly penalized by the data exchange process. Currently, when financial data are dematerialized, they are exchanged in a multitude of formats: Excel files, free text, PDF, etc. Often not much more suitable for processing than photocopying and limited to certain platforms, these formats prove unsuitable for the exchange of information between programs, for analysis, comparison and presentation of reports to users. So far, despite a strong tendency to use XML syntax, attempts at convergence have struggled to generalize and apply to many sectors and contexts. In recent years, reporting requirements have led to a significant increase in the cost of using financial systems. The use of XBRL technology, using XML syntax, supported by many players in the world of finance, the software industry and adapted to reporting, can constitute the solution. Many governments, regulators, financial institutions are already using XBRL or have pilot projects in place. This document specifically targets XBRL. This technology, which is now recognized by the entire software industry, provides tremendous benefits for data exchange, storage, research and processing.